THE DICHOTOMY OF INFORMATION TECHNOLOGIES IN PROFESSIONAL TRAINING OF FUTURE IT SPECIALISTS: THE SUBJECT AND THE MEANS OF INSTRUCTION - Malykhin, Oleksandr; Aristova, Nataliia; Kovalchuk, Vasyl; Popov, Roman; Yarmolchuk, Taras (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The study shows some preferences in the choice of training and learning strategies in university educational process aimed at forming future IT-specialists’ digital competence as the main indicator of their professionalism in IT-sphere considering information technologies as being the subject and the means of instruction. The use of information technologies results in rethinking of existing approaches to organizing the educational process of higher school especially when it comes to training future IT-specialists. Information technologies integrated into all spheres of human activities and widely applied to support different industries in commercial, private and public sectors cause ever-growing demand for highly-qualified IT-specialists. In the study the authors consider the range of learning strategies used in the educational process for boosting effectiveness of IT-specialists’ digital competence formation as the main indicator of their professionalism in IT-sphere. The study was carried out among 164 future IT-specialists at three higher education institutions in Ukraine from February to May 2019. The researchers found out that all the respondents used contemporary information technologies for learning IT-disciplines, namely, all the students (100.00%) use contemporary information technologies in their formal learning, 68.80% − in their non-formal learning, 18.30% − in a wide range of educational activities that could be regarded as informal learning and only 13.20% − combining informal and non-formal learning. The obtained data were analyzed qualitatively and quantitatively. As the core result of conducted research the component matrix of learning strategies was developed showing their hierarchy depending on three factors chosen i.e. traditional, self-directed and collaborative learning.